Changing patterns in recruitment to stipendiary ministry: A study in psychological profiling. Issue 4 (July 2018) - Francis, Leslie J.; Smith, Greg
This article tests the hypothesis that the Church of England may be recruiting into stipendiary ministry a different psychological profile of clergy to respond to the changing demands of parochial ministry. Using the Francis Psychological Type Scales, the profiles of 90 male and 35 female curates under the age of 40 ordained into stipendiary ministry in 2009 and 2010 were compared with the profiles of 626 clergymen and 237 clergywomen reported in a study published in 2007. The major difference between the two groups concerns the significantly higher proportions of sensing types and the Epimethean temperament (SJ) among the curates. These shifts in psychological type and temperament promise a Church for the future that is more tightly managed but less inspirational and less responsive to transformative development.